Day is Done - Yarrow, Peter, 1938-; Sweet, Melissa, 1956- (New York : Sterling, 2009)
Animal parents reassure their children that all will be well when the day is done, despite their sorrow and fear.
"Includes a three-song CD recorded by Peter Yarrow (of Peter, Paul & Mary) with Bethany Yarrow"--Jacket.
Keywords: Parent-child relationship -- Songs; Animals -- Songs; Songs; Audiobooks